Study the usefulness of cartridge based NUCLEIC acid amplification test in bronchoalveolar lavage samples in the diagnosis of smear-negative/non sputum producing patients with suspected tuberculosis - Kumar, K. Raj; Reddy, Sony; Vamsi, Raghu (International Journal of Research in Medical Sciences, 2019)
Background: The aim of study is to evaluate the diagnostic value of the CBNAAT in BAL samples of smear negative for AFB or who could not produce an expectorated sputum sample. Methods: A prospective and observational study of in patient and out patient department in Department of Pulmonary Medicine of Chalmeda Anand Rao Institute of Medical Sciences, Karimnagar during the period November 2017 to November 2018. Results: Bronchoalveolar lavage cartridge based nucleic acid amplification test in bronchoalveolar lavage was done for 60 samples of patients who were having history and chest x-ray suggestive of pulmonary tuberculosis with sputum AFB negative. Out of these sputum negative samples 25 were BAL CBNAAT positive and rest were negative. Conclusions: CBNAAT adds significantly to the diagnostic yield of PTB in comparison to sputum smear microscopy. It has additional advantage of identifying rifampicin resistance with high sensitivity and specificity.